Menelusuri Jejak Otak dan ‘Aql Dalam Alquran Perspektif Neurosains dan Pendidikan Islam di Era Pandemi Covid-19 - Mohammad Jailani; Suyadi; Dedi Djubaedi (TADRIS: Jurnal Pendidikan Islam, 2021)
The purpose of this research analyzing Islamic education learning in the era of the Covid-19 pandemic from the perspective of Neuroscience. The development of the learning model of Islamic education and neuroscience in this modern era is in line with research on neuroscience in Islamic education discourse, which so far has only been understood as edentically with medical science, namely health in the brain. while Neuroscience is integrated with Islamic education in theological aspects (Alquran and hadith), historical, academic and theoretical. This research data is sourced through literature observations related to descriptions of scientific journals and examination of references to research works, both manually and digitally, which focus on discussing Islamic education learning in the new discourse of Neuroscience. This research is a literature study using qualitative methods. The results of the study prove that Neuroscience has traces in the field of Islamic education thought theologically has a Neorubiological basis in the Qur'an surah al-Alaq verses 15-16 with the keyword "nasyiyah" (crown), historically Neuroscience is closely related to Islamic philosophy, fiqh and ushul fiqh. Academically and theoretically related to the concept of 'Aql and Qolb in the Koran and hadith. Its derivatives gave rise to the hybridization of Neuroscience and Islamic education. This will have broad implications for the learning model during the Covid-19 pandemic. Academically and theoretically related to the concept of 'Aql and Qolb in the Koran and hadith. Its derivatives gave rise to the hybridization of Neuroscience and Islamic education. This will have broad implications for the learning model during the Covid-19 pandemic. Academically and theoretically related to the concept of 'Aql and Qolb in the Koran and hadith. Its derivatives gave rise to the hybridization of Neuroscience and Islamic education. This will have broad implications for the learning model during the Covid-19 pandemic.